Spleen Tyrosine Kinase Inhibition Modulates p53 Activity. (19th September 2017) - Althubiti, Mohammad
Spleen tyrosine kinase (SYK) is a cytoplasmic enzyme that promotes survival and proliferation of B cells. SYK inhibition has shown promising results in the treatment of arthritis and chronic lymphocytic leukemia (CLL). However, in other context, it has been shown that SYK overexpression in epithelial cancer cells induced senescence in p53-dependent mechanism, which underscored its antineoplastic activity in vitro. Here, we show that SYK was induced in response of DNA damage in parallel with p53 levels. In addition, using chemical inhibitors of SYK reduced p53 levels in HCT116 and HT1080 cell lines, which underlines the role of SYK inhibition on p53 activity. Furthermore, SYK inhibition modulated the cell growth, which resulted in a decreasing in cell death. Interestingly, SYK expression showed a positive prognosis in patients with solid tumors in correlations with their survival rates, as expected negative correlation was seen between SYK expression and survival rate of patients with CLL. In conclusion, these findings demonstrate that SYK inhibition modulates p53 expression and activity in HCT116 and HT1080 cells. Reconsidering using of SYK inhibitors in clinical setting in the future should be evaluated carefully in accordance with these findings to prevent the formation of secondary malignancies.